Antibacterial Activity of Silver Nanoparticles Synthesized from Plant Latex - Saleh, Ghada Mohammed; Najim, Shaymaa Suhail (Iraqi Journal of Science, 2020)
Nanoparticles produced by plants are preferred in the medical field for its safe and unpolluted product; it is also accepted as an ecofriendly, non-expensive, and non-toxic nanomaterial. In this study, silver nitrate was successfully used to produce silver nanoparticles (AgNPs) by the use extractsof 4 different latex-producing plants which belong to 2 families (Moraceae and Euphorbiaceae). The synthesis was proved by Atomic Force Microscopy (AFM).The sizes of the AgNP grains were estimated by Granularity Cumulating Distribution (GCD). The results revealed the production of AgNPs in different sizes of 103 and 82 nm using the Moraceae family and 77 and74nm using the Euphorbiaceae family.Antibacterial activity was also detected against both Gram positive and Gram negative pathogenic bacteria using the well diffusion assay. In conclusion, this source of nanoparticles can be a very useful industrial project in a goal to find new safe and economic alternatives to antibiotics.